Fast Microwave-Assisted Green Synthesis of Silver Nanoparticles Using Low Concentration of Seminyak (Champeria sp.) Leaf Extract - Muhammad Bagas Ananda; Fathan Aditya Sanjaya; Tami Bachrurozy; Helmi Majid Ar Rasyid; Anggraini Barlian; Akfiny Hasdi Aimon; Fitriyatul Qulub; Prihartini Widiyanti; Arie Wibowo (Indonesian Journal of Chemistry, 2023)
Silver nanoparticles (AgNPs) are fascinating materials for biomedical applications thanks to their strong antibacterial activity and biocompatibility. This study applied the green synthesis method using 0.5 wt.% Seminyak leaf extract and assisted with one min microwave irradiation to enhance AgNPs formation. Extremely small sizes AgNPs with an average particle size of 9.1 ± 4.1 nm and spherical shapes were obtained. The synthesized AgNPs displayed potent antibacterial activity against Escherichia coli and Staphylococcus aureus bacteria with a zone of inhibition of 12.3 ± 0.1 and 13.7 ± 0.7 mm, respectively. The MTT assay results demonstrated that the cells’ viability of the obtained AgNPs was 88.5 ± 7.0 %, implying biocompatibility for biomedical applications.